The Determination of Lipide- Soluble Vitamin Contents of Some Astragalus Taxa by Using HPLC - Bahşi, Muammer; Kurşat, Murat; Emre, İrfan; Ökkeş,; Yılmaz, Okkes; Yilmaz, (My University, 2019)
The goal of current study is to contribute the biochemical studies of five Astragalus (Astragalus anthlloides,Astragalus hirsutus, Astragalus campylorhynchus, Astragalus cephalotes var. cephalotes, Astragalus odaratus)species by determining the lipide-soluble vitamin contents based on HPLC analyse. Current study showed that A.anthlloides (208,95±4,09 µg/g) and A. hirsutus(200,9±2,8 µg/g) have high ?-tocopherol content. Also, D3 vitamincontent of studied Astragalus species were found between 2,94±0,18 µg/g (Astragalus odaratus) and 12,53±,495µg/g (Astragalus anthlloides). On the other hand, ?-tocopherol content of Astragalus species have detectedbetween 3,99±0,14 µg/g (Astragalus campylorhynchus) and 11,9±0,66 µg/g (Astragalus cephalotes var.cephalotes). However, it was found that A. hirsutus only have beta caroten content (3,55±0,43 µg/g) among studiedspecies. On the other hand, it was found that r-tocopherol, a-tocopherol acetate, D2, K1, retinol and retinol acetatecontents were lowest amounts or absent.
Keywords: Biyoloji; Spektroskopi; Kimya; Tıbbi